Benefits And Challenges of The Use of Generative AI in English Learning in Higher Education: Students’ Voices - Puspa, Adelia; Jayanti, Fernandita Gusweni; Haryana, Lia (International Journal of Innovation and Education Research, 2025)
This research aims to examine how students perceive generative AI technology, such as ChatGPT, in the context of English language learning. The focus of this research is on how familiar students are with this technology, how open they are to using it, as well as the benefits and challenges that may arise, including the proper usage concerning English language learning. In an online survey involving 293 students from various majors at 3 universities in Bengkulu, Indonesia, it was found that the majority of students had a positive view towards the use of GenAI in English language learning. They realize that this technology can help them in personalized learning, providing assistance in writing, completing assignments, and also in research and analysis. However, despite the many advantages, students also expressed some concerns. They are concerned about the accuracy of the information generated and ethical issues. By understanding these student perspectives, educators and policymakers can better tailor the use of GenAI to meet their needs and concerns, as well as promote better English learning outcomes. Keywords: Benefits, Challenges, English Learning, Generative AI